Protective and risk factors of problematic smartphone use in preteens using panel study on Korean children - Yun, Jungim; Han, Gyumin; Son, Hyunmi (Frontiers in Psychiatry, 2022)
Background: Increased smartphone use by children and adolescents places them at higher risk of overdependence. The problematic smartphone use of preteens is rapidly increasing. The preteen period is one of considerable developmental change and the influence of problematic smartphone use should be identified by reflecting on this change and considering its social psychological factors. Methods: This study employed a secondary analysis using data from the 10th (2017) to 11th (2018) wave of the Panel Study on Korean Children. STATA/BE 17 was used to analyze the panel logit model. Among the 1,286 participants aged 9–10 from the Panel Study on Korean Children, 342 with complete responses were selected as the participants of this study. Results: The risk group for problematic smartphone use showed an increase from 126 in 2017 to 149 in 2018. Factors influencing risk of preteens’ problematic smartphone use were the child’s externalizing problems (p=.015) and permissive parenting behavior (p=.003). Protective factors influencing preteens’ problematic smartphone use were peer communication (p=.023), parental supervision (p=.020), and authoritative parenting behavior (p=.001). Conclusions: Preteens with externalizing problems are at a higher risk for problematic smartphone use and are therefore a group to be observed with caution. It is also required to guide them to form good relationships with friends. Finally, in the problematic smartphone use of preteens, parents are both a protective factor and a risk factor. Therefore, guidance is required so that children can behave properly.